ANALISIS YURIDIS PENGAKUAN KEBERADAAN MASYARAKAT HUKUM ADAT DALAM UNDANG-UNDANG NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL - Hapsari, Regita Kurnia (Fakultas Hukum Universitas Sebelas Maret, 2014)
AbstractThis research was conducted to obtain an overview of the legal recognition of indigenous peoples in the presence of Law Number 20 of 2003 on the National Education System. The Law materials are Law Number 20 of 2003 on the National Education System and some publications are assembled with national education system. Legal materials collected through document study further analyzed and interpreted into text that is the result of the analysis of the author. Discussion of the results showed education to guarantee the existence of indigenous communities as a form of restriction. Chapter after chapter in the Law Number 20 of 2003 on National Education System which contain customary communities ensure education for indigenous and tribal peoples, but his form is not flexible precisely because everything must not be contrary to the principle of state.Keywords: Indigenous people, National Education System